KONSEP PENDIDIKAN AKHLAK SEJAK DINI MENURUT AL-GHAZALI - Almanna Wassalwa (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2017)
Early childhood has a unique character, both physically and mentally, therefore Early Childhood Education (ECE) teacher needs to be adapted a set of teaching strategies and teaching methods for early childhood that should be adjusted to the unique characters which are owned by early childhood students. Because that teaching methods that applied by teacher will strongly affect to the success of the teaching and learning process. The use of teaching methods that appropriate to the characters of the childrens will be able to facilitate, not only the optimal development of potentials and abilities of childrens, but also the positive growth of attitude and behavior of childrens. According to al-Ghazali, there are two ways in teaching morals. They are first, mujahadah as the habituation to practice in righteous deeds and second, istiqomah as the act was done in repeated.